(3TQM EVGAI GdOLfI Yf YbGFO Cgd GdSfIs - (3eMeO Hf GdeNJGQ Hf GdCYeTs; (3CMeO Hf eMeO Hf CMeO Hf jMji Hf YHO GdQMef GdebQj , CHh GdYHGS,J (B1041 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi HaVdg hHYO aGdESJYGfg HGdehdi GdcQje Ydi TQM EVGAI GdOLfI hgj aUjOI ai NeS eGFI HjJ , JTJed Ydi aUhd ef bhGYO Yde GdJhMjO, hCUhd LeYJ ef Gdaf YRR ahGFOg s
(3BNQgG (B:s
(3aCfJ JQi gPG GdaVd GdYXje efg dLejY GdNdb ai GdeMTQ GdPi ELJeY ajg LejY GdNdGFb GdYdhjI hGdSadjI hgPG BNQ eG jSQ Gddg JYGdi HaVdg hefg ced s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3fSNI eQbeIs
(3cJHgG fGSNgG ddMHjH Hf Ydi s
(3eUMMIcJH GdeJf HGdMeQI s
(3bQf GdfSN (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds